PENGARUH PENYULUHAN KESEHATAN REPRODUKSI REMAJA DENGAN METODE CERAMAH TERHADAP PENGETAHUAN DAN SIKAP PADA SISWA SMKN 1 KOTA BUKITTINGGI - Oktaliza Elektrina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Reproductive health problems of adolescents in Indonesia areproblems around sexuality, HIVAIDS, drugs, and abortion. The teenager’slow knowledgeabout reproductive health will affect attitudes that will be carried out by adolescents related to reproductive health. Adolescent reproductive health problems occur because of the lack of education that adolescents get to reproductive health. The study aims to determine the effect of adolescent reproductive health counseling with the lecture method on students knowledge and attitudes SMKN 1 Bukittinggi City. This type of research is an experimental stdy using pretes and posttest (one group pretest and posttest design). The study population was 115 students. Measuring instrument in this univariat and bivariate, non parametris data distribution with Wilcoxon test. Risk factors of the study of the Wilcoxon test obtained results asymp.sig (2-tailed)=0,000 at significant rates0,05. Because of the resultsasymp.sig knowledge and attitude smaller than 0,05 means H0 rejected so there is the influence of adolescent reproductive health counseling with the lecture method on students knowledge and attitudes. In this study based on the analysis of the tests that have been carried out there is the effect of adolescent reproductive health counseling on the knowledge and attitudes of respondents after intervention. The conclusion of this study is the lack of adolescent knowledge of reproductive health.Keywords: Reproductive Health Counseling; Lecture Method; Knowledge; Attitude.